Recombinant biosynthesis of bacterial cellulose in genetically modified Escherichia coli - Buldum, Gizem (Bioprocess Biosyst Eng, 2017)
Bacterial cellulose (BC) exhibits unique properties such as high purity compared to plant-based cellulose; however, commercial production of BC has remained a challenge, primarily due to the strain properties of cellulose-producing bacteria. Herein, we developed a functional and stable BC production system in genetically modified (GM) Escherichia coli by recombinant expression of both the BC synthase operon (bcsABCD) and the upstream operon (cmcax, ccp Ax). BC production was achieved in GM HMS174 (DE3) and in GM C41 (DE3) by optimization of the culture temperature (22 °C, 30 °C, and 37 °C) and IPTG concentration. BC biosynthesis was detected much earlier in GM C41 (DE3) cultures (3 h after IPTG induction) than those of Gluconacetobacter hansenii. GM HMS174 (DE3) produced dense fibres having a length of approximately 1000–3000 μm and a diameter of 10–20 μm, which were remarkably larger than the fibres of BC typically produced by G. hansenii. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00449-017-1864-1) contains supplementary material, which is available to authorized users.